1988
DOI: 10.1126/science.3187533
|View full text |Cite
|
Sign up to set email alerts
|

Ovothiol Replaces Glutathione Peroxidase as a Hydrogen Peroxide Scavenger in Sea Urchin Eggs

Abstract: Despite its potential toxicity, H2O2 is used as an extracellular oxidant by Stronglylocentrotus purpuratus eggs to cross-link their fertilization envelopes. These eggs contain 5 mM 1-methyl-N alpha,N alpha-dimethyl-4-mercaptohistidine (ovothiol C), which reacts with H2O2. In consuming H2O2 and being reduced by glutathione, ovothiol acts as a glutathione peroxidase and replaces the function of the enzyme in eggs. The ovothiol system is more effective than egg catalase in destroying H2O2 at concentrations produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 15 publications
2
80
0
1
Order By: Relevance
“…It is evident from what is presently known that ovothiol A in the presence of trypanothione and its reductase would constitute an effective trypanothione peroxidase system [25]. In this regard it is of interest that trypanothione peroxidase activity was not detected in extracts of Trypanosoma cruzi [7].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It is evident from what is presently known that ovothiol A in the presence of trypanothione and its reductase would constitute an effective trypanothione peroxidase system [25]. In this regard it is of interest that trypanothione peroxidase activity was not detected in extracts of Trypanosoma cruzi [7].…”
Section: Discussionmentioning
confidence: 81%
“…It was subsequently found that 4-mercaptohistidines occur in millimolar concentrations in the eggs of a variety of echinoderms and molluscs [21,231. Ovothiols and related model mercaptohistidines were shown to be several tenfold more efficient than glutathione as free radical scavengers [24] and to react with hydrogen peroxide at five times the rate measured with glutathione [25]. It was therefore proposed that the high concentrations of ovothiols in the eggs of marine invertebrates serve to protect the contents of the oocyte against oxidative damage which could result from the release of hydrogen peroxide in the oxidative burst triggered by fertilization [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSH Px-like activity of ebselen results from two consecutive reactions: the oxidation of the thiols by peroxide and the reduction of the disulphides by glutathione. The consumption of NADPH 11,12) upon the addition of H 2 O 2 in the absence of test compounds was 0.8 mM NADPH/min. There was no detectable activity with the solvent DMSO alone.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Ovothiols are considered to be the most potent natural antioxidants, 7,8 presumably due to their low thiolate basicity and the concomitant ready oxidizability. They act as protective antioxidants 9,10 in many parasitic protozoa. [11][12][13][14][15] These peculiarities have attracted pharmaceutical interest to create prospective antitrypanosomal chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%